Ponzi schemes and its prevention: insights from Malaysia / Eley Suzana Kasim ... [et al.] - Kasim, Eley Suzana; Md Zina, Norlaila; Mohd Padil, Hazlina; Omar, Normah (Universiti Teknologi MARA, Shah Alam: Accounting Research Institute (ARI), 2020)
A Ponzi scheme is a fraudulent investing scheme which promises high rates of return with little risk to investors. The scheme has led to a substantial amount of financial leakages in recent years. Despite warnings by the law enforcement agencies and regulators, many have unfortunately fallen victim. Hence, the current measures are limited in preventing the fraudulent schemes. Therefore, the present study aimed to identify the influencing factors for joining Ponzi schemes by examining the modus operandi used, profile of victims and fraudsters and to investigate the current measures in preventing Ponzi schemes in Malaysia. This study employed a qualitative methodology with semi-structured interviews and document reviews to collect data. Interviews involving eight interviewees with regulators, enforcers, and victims revealed that prevention of Ponzi schemes should be addressed holistically by examining the modus operandi used, profile of victims and fraudsters. Findings further indicated that the prevention measures are led by three core elements consisting of education, regulations and enforcement. Additionally, education is the best approach to ensure an effective preventive strategy which needs to be supported by a specific regulations on Ponzi schemes. This study provides recent evidence on Ponzi schemes and valuable insights for future development of preventive measures.